Multidrug-resistant Klebsiella quasipneumoniae subsp. similipneumoniae carrying blaNDM-blaCTX-M15 isolated from flies in Rio de Janeiro, Brazil. (March 2021) - Carramaschi, Isabel N.; dos S. B. Ferreira, Vítor; Chagas, Thiago P.G.; Corrêa, Lais L.; Picão, Renata C.; de C. Queiroz, Margareth M.; Rangel, Karyne; Jardim, Rodrigo; da Mota, Fabio F.; Zahner, Viviane
Highlights: A MDR strain was isolated from a fly collected next to a public hospital. K. quasipneumoniae subsp. similipneumoniae carries a bla NDM-1 on Tn 3000 K. quasipneumoniae subsp. similipneumoniae harboured numerous resistance genes Flies can be involved in the spread of antibiotic resistance. Abstract: Objectives: Flies have been implicated in the dispersal of medically important bacteria including members of the genus Klebsiella between different environmental compartments. The aim of this study was to retrieve and characterize antibiotic-resistant bacteria from flies collected near to hospitals. Methods: Flies were collected in the vicinity of medical facilities and examined for bacteria demonstrating phenotypic resistance to ceftriaxone, followed by determination of phenotypic and genotypic resistance profiles. In addition, whole genome sequencing followed by phylogenetic analysis and resistance genotyping were performed with the multidrug-resistant (MDR) strain Lemef23, identified as Klebsiella quasipneumoniae subsp . similipneumoniae . Results: The strain Lemef23, classified by multiple locus sequence typing as novel ST 3397, harboured numerous resistance genes. The bla NDM was located on a Tn 3000 element, a common genetic platform for the carriage of this gene in Brazil. Inference of phylogenetic orthology of strain Lemef23 and other clinical isolates suggested an anthropogenic origin. Conclusions: The findings of this study support the role of flies as vectors of MDR bacteria of clinical importance and provide the first record of bla NDM-1 and bla CTXM-15 in a Brazilian isolate of K. quasipneumoniae subsp. similipneumoniae, demonstrating the value of surveying insects as reservoirs of antibiotic resistance.